2023
DOI: 10.3389/fmicb.2022.1070876
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbial communities and rice yield to nitrogen reduction with green manure application in karst paddy areas

Abstract: Fertilizer application practices are one of the major challenges facing agroecology. The agrobenefits of combined application of green manure and chemical fertilizers, and the potential of green manure to replace chemical fertilizers are now well documented. However, little is known about the impact of fertilization practices on microbial communities and tice yield. In this study, the diversity of bacterial and fungal communities, symbiotic networks and their relationship with soil function were analyzed in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
2
7
0
Order By: Relevance
“…This suggests that the use of MV and RS could decrease the amount of chemical fertilizer required by 40% while maintaining high yields, and the yield of double rice cropping was higher in the MV and RS treatments than in the CF treatment, which was similar to another study [24]. This was because both high biomass C and N inputs increase the organic matter and nutrients in the soil, improve soil structure, and promote microbial activity, thereby favoring the growth and development of rice which leads to enhanced rice productivity [4,16]. The mineral N fertilizers were able to quickly provide nutrients for crop growth, and we found that the yield under the N 60 level was lower than that under the N 100 level under the same organic addition treatment.…”
Section: Co-incorporation Of Chinese Milk Vetch and Rice Straw Increa...supporting
confidence: 77%
See 2 more Smart Citations
“…This suggests that the use of MV and RS could decrease the amount of chemical fertilizer required by 40% while maintaining high yields, and the yield of double rice cropping was higher in the MV and RS treatments than in the CF treatment, which was similar to another study [24]. This was because both high biomass C and N inputs increase the organic matter and nutrients in the soil, improve soil structure, and promote microbial activity, thereby favoring the growth and development of rice which leads to enhanced rice productivity [4,16]. The mineral N fertilizers were able to quickly provide nutrients for crop growth, and we found that the yield under the N 60 level was lower than that under the N 100 level under the same organic addition treatment.…”
Section: Co-incorporation Of Chinese Milk Vetch and Rice Straw Increa...supporting
confidence: 77%
“…The report pointed out that if full N fertilizer was used together with green manure, it might lead to a decrease in microbial network complexity, reducing the types and quantities of microorganisms. Also, excessive chemical N fertilizer application might cause a decrease in soil pH, further affecting the growth of microorganisms [16]. Therefore, to protect the environment and promote the sustainable development of agriculture, it is necessary to reduce the application of chemical N fertilizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Liu et al, 2021a) found that the addition of organic fertilizers with inorganic fertilizers in different ratios could increase soil organic matter and total nitrogen (TN) content and alleviate soil acidification to some extent. In a recent study by Meng et al (2022), organic fertilizers significantly increased the soil organic matter content and were able to improve the pH of acidic soils compared to the application of chemical fertilizers, and the same results were obtained by Cao et al (2017) and Pu et al (2022). Overall, the combination of organic fertilizer and controlled irrigation techniques can reduce the total rate of nitrogen application (Koothan et al, 2014), effectively improve soil nitrogen effectiveness in rice fields, reduce leaching losses of fertilizer nitrogen (Zhang et al, 2018) and improve sustained water and nutrient uptake by crops (Zhao et al, 2022), thus promoting yield (Liao et al, 2020).…”
Section: Introductionsupporting
confidence: 57%
“…The application of green manure on farmland is useful for increasing organic matter and nutrition in the soil and improving the soil characteristics that have a positive impact on production. Green manure provides a source of plant nutrients, and can be used as an alternative to chemical fertilizers, which is extremely important in agricultural development (Pu et al, 2023). One plant that can be found in abundance and grows well in highland areas is C. odorata, although its benefits in farming are not yet widely known (Ahmad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%